Complex Independent Laboratory Tests to Signify Fuel Economy and Emissions under Real World Driving - Boretti, Albert; Lappas, Petros (Advances in Technology Innovation, 2019)
We discuss the shortcomings of the current European Union emission rules, which are not likely to produce any improvement of fuel economy and emissions during real-world driving vs. the pre-Diesel gate rules, because of flaws in the prescribed laboratory and on-the-road tests. The present chassis dynamometer emissions certification test is oversimplified, not representative, and not properly performed. The simple addition of generic on-the-road real-world driving tests does not help, because these tests have poor accuracy and repeatability. Therefore, we suggest the use of a more realistic, complicated, suite of driving cycles, to be rigorously performed with chassis dynamometer equipment by independent bodies, rather than the Original Equipment Manufacturers (OEMs). Additionally, we suggest that emission limits be revised, to permit the optimal mix between different engine technologies and different fuels.